Evaluating The Effects of Chitin and Its Analogues with Improved Solubility on Human Hexokinase Isoform 2 for Dengue Treatment via Virtual Screening Analyses - Ahmad Fuad, Fazia Adyani; Azizi, Nur Aqilah Husna; Abdul Wahab, Mohd Firdaus; Shaarani, Siti Hajar Noor; Tengku Abdul Rashid, Tengku Rogayah (Universitas Jenderal Soedirman, 2025)
ABSTRACT. Dengue fever, a vector-borne disease caused by dengue virus (DENV) is currently endemic in over 100 countries. Despite being pronounced as one of the WHO’s ten threats to global health in 2019, there are currently no antiviral therapies for dengue fever available in the market. Hence, finding the cure for dengue is still currently under pursuit. Chitin, the most abundant biopolymer after cellulose was shown to be one of the potential inhibitors of human hexokinase isoform 2 (HK2), which can subsequently impair DENV upon their replication in human bodies. However, the insolubility characteristics of chitin may cause issues in the subsequent in vitro and in vivo analyses. This project aims to screen for analogues of chitin with improved solubility and high binding affinity when interacting with HK2 via an in silico approach. In this study, ligand-based screening was conducted to find the analogues of chitin, while solubility prediction was performed to predict the solubility of the analogue compounds. Subsequently, structure-based screening was conducted via molecular docking to observe the binding affinity of the analogues with HK2. As a result, a compound known as β-N-acetyl-D-galactosamine was identified as an analogue of chitin with a similarity score of 99.47%. The compound also possessed high solubility (higher than 0.06 mg/ml) and negative LogP value (-3.22), which indicates a higher preferential solubility in water. In addition to that, toxicity prediction test exhibited that β-N-acetyl-D-galactosamine falls under class 6 of toxicity, indicating that it is a non-toxic compound. Thus, a potential drug that may treat dengue fever and safe to be administered to patients can be potentially developed by using this compound. Keywords: Chitin, chitin analogues, dengue fever, dengue treatment, hexokinase isoform 2